Tissue N‐Glycan Analysis Using LC‐MS, MS/MS, and MSn. Issue 7 (27th July 2021) - Suzuki, Noriko
Abstract: Tissue glycans usually contain various structures, from simple to highly complicated, in different quantities. N ‐Glycans are particularly heterogeneous, with up to pentaantennary structures, different branch sequences, and several isomeric structures. 2‐Aminopyridine (PA) tagging on released N ‐glycans is useful for separating isomers and to quantitatively analyze both the major and minor glycan structures in tissues using reversed‐phase liquid chromatography (LC)−mass spectrometry (MS) and MS/MS analysis. Because the structural differences of PA‐ N ‐glycans influence their retention on a reversed‐phase C18 column, it is easy to deduce the core structure, including core Fuc and bisecting GlcNAc as well as the branching pattern of each PA‐ N ‐glycan, based on the results of elution position, full MS, and MS/MS analysis. If more detailed structural analysis is required, combining sequential exoglycosidase digestions, sialic acid linkage−specific alkylamidation (SALSA), and/or SALSA/permethylation is useful for determining glycosidic linkages of branches. This article includes detailed protocols for the preparation of N ‐glycans released from glycoproteins/glycopeptides by glycoamidase F or hydrazinolysis, PA‐tagging of N ‐glycans, fractionation with anion‐exchange chromatography, and chemical or enzymatic modifications of PA‐ N ‐glycans, as well as reversed‐phase LC‐MS, MS/MS, and MS n analysis of PA‐ N ‐glycans from tissues. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of released N ‐glycans from tissue samples using glycoamidase F Alternate Protocol : Preparation of released N ‐glycans from tissue samples by hydrazinolysis Basic Protocol 2 : PA‐tagging of N ‐glycans and sample cleanup Support Protocol 1 : Monitoring of PA‐ N ‐glycans using normal‐phase HPLC Basic Protocol 3 : Anion‐exchange chromatography of PA‐ N ‐glycans Basic Protocol 4 : Sequential exoglycosidase digestions Basic Protocol 5 : Determination of Sia‐linkages by SALSA Support Protocol 2 : Cotton‐HILIC solid‐phase extraction to remove reagents for alkylamidation Basic Protocol 6 : Sequential modifications of glycans with SALSA and permethylation Basic Protocol 7 : LC‐MS and MS/MS analysis of PA‐ N ‐glycans (before permethylation) Basic Protocol 8 : LC‐MS, MS/MS, and MS n analysis of PA‐ N ‐glycans (after permethylation)